Sishankamrata in the Indonesian State Defense and Security System from the Beginning of Independence to the Reform Period - Ladlul Muksinin (Universitas Islam Negeri Walisongo Semarang, 2020)
The debate regarding the concept of the Indonesian state defense and security system is still a fundamental subject of mathematic since the independence era until the reform era. For example, regarding the definition of national security with state security, defense function with security functions, regulations, and many more. For this reason, this paper will discuss how the dynamics of the Sishankamrata in the State Defense and Security System (Sishanneg) the independence era the reform era. This paper discusses that the National Defense System (Sishaneg) is believed to still need to be maintained in national defense and security policies. The concept of Sishankamrata develops its form of defense through the involvement of all components of the citizenry, territorial integrity, natural resources, and other means that have been prepared in advance. This system also makes defense integration (military and non-military) stronger, more respected, and has higher deterrence. So that in the era of reform, it was explicit that the concept of Sishankamrata was considered powerful enough so that it was still maintainedExplicitly in the reform era after the amendment of the 1945 Constitution of the Republic of Indonesia, the concept of Sishankamrata was still maintained and wa considered quite effective.[]Perdebatan mengenai konsep sistem pertahanan dan keamanan negara Indonesia masih menjadi problematika mendasar sejak masa kemerdekaan hingga masa reformasi. Misalnya mengenai pengertian keamanan nasional dengan keamanan negara, fungsi pertahanan dengan fungsi keamanan, regulasi dan masih banyak lagi. Untuk itu tulisan ini akan mendiskusikan bagaimana dinamika Sistem Pertahanan Keamanan Rakyat Semesta (Sishankamrata) dalam Sistem Pertahanan dan Keamanan Negara (Sishanneg) dari awal kemerdekaan pasca reformasi. Tulisan ini akan mendiskusikan bahwa Sistem Pertahanan Nasional (Sishaneg) perlu untuk tetap dipertahankan dalam kebijakan pertahanan dan keamanan nasional. Konsep Sishankamrata ini mengembangkan bentuk pertahanannya melalui keterlibatan seluruh komponen warga negara, kesatuan wilayah, sumber daya alam, serta sarana lainnya yang lebih dulu dipersiapkan. Sistem ini juga melakukan integrasi pertahanan (militer dan nirmiliter) menjadi lebih kuat, lebih disegani, dan lebih tinggi daya tangkalnya. Secara eksplisit pada era reformasi setelah UUD NRI Tahun 1945 diamandemen, konsep Sishankamrata ini masih dipertahankan dan dianggap cukup efektif.